A Panel Analysis of Crude Oil Exports and Poverty Reduction in African Oil Producing Countries: Implication for the Sustainable Development Goal One - Imeokparia, Lawrence; Peter, Olaoye Olusegun; Bello, Bahiru Akande; Osabohien, Romanus; Aderemi, Timothy Ayomitunde; Gershon, Obindah; Aaron, Disi; Abidemi, Alejo (International Journal of Energy Economics and Policy, 2023)
The objective of this research is to determine the impact of oil exports on poverty reduction in African oil exporting countries. The study spanned over 30 years, from 1991 to 2020, and relied on secondary data extracted from ten (10) highest oil-producing countries in Africa. The human development index (HDI) was used as a proxy for poverty reduction. The Panel ARDL technique was used to analyse the data. According to the findings of this study, the oil exports using revenues from oil exportation and total annual barrels of oil produced had a beneficial impact on human capital development and thus reduced poverty in the selected African oil-exporting countries. The impact of total revenue from oil exports, on the other hand, was statistically insignificant, although the impact of total annual barrels of oil produced was not. As a result of these findings, the study finds that in the long run, oil revenues had a positive impact on poverty reduction in oil-exporting African countries, although not to a significant extent. This implies that the study does not provide empirical evidence to support the existence of resource curse hypothesis. In view of the above findings, this study recommends that the policymakers in African oil exporting countries should utilize the proceeds from the oil exports for the human development oriented programmes that have trickle down effects on poverty reduction in these countries.